2022
DOI: 10.1097/sla.0000000000005452
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Determined by Skeletal Muscle Index Predicts Overall Survival, Disease-free Survival, and Postoperative Complications in Resectable Esophageal Cancer

Abstract: Background: Sarcopenia has been identified as a prognostic factor among certain types of cancer. In esophageal cancer, patients are at increased risk of malnutrition and sarcopenia, ultimately contributing to poor outcomes. A systematic review was conducted to determine whether sarcopenia, defined by the skeletal muscle index, is predictive of overall survival, disease-free survival, and postoperative complications in resectable esophageal cancer. Materials and Methods: A systematic search of MEDLINE, EMBASE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 54 publications
2
31
2
Order By: Relevance
“…Given that sarcopenia is classified at the staging CT scan in the majority of studies included in the meta‐analysis, the results suggest that the prognostic impact of sarcopenia is present throughout disease progression. This notion is corroborated by a recently published systematic review on sarcopenia in resectable oesophageal cancer 26 …”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Given that sarcopenia is classified at the staging CT scan in the majority of studies included in the meta‐analysis, the results suggest that the prognostic impact of sarcopenia is present throughout disease progression. This notion is corroborated by a recently published systematic review on sarcopenia in resectable oesophageal cancer 26 …”
Section: Discussionmentioning
confidence: 53%
“…This notion is corroborated by a recently published systematic review on sarcopenia in resectable oesophageal cancer. 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 However, they only included 11 studies with 1520 patients, and the selected studies were dated till 2018. In addition, Uzair et al 12 had conducted a meta‐analysis focusing on sarcopenia determined by SMI. They reported that sarcopenia was associated with poor survival outcomes in EC patients who had undergone surgical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al conducted a meta‐analysis to detect sarcopenia effects on long‐term survival of patients with EC, 11 however, they only included 11 studies with 1520 patients, and the selected studies were dated up to 2018. In addition, Uzair et al 12 had conducted another meta‐analysis, including 21 studies published before 2020 about sarcopenia assessed solely by CT‐based body imaging and included patients who underwent surgery with curative intent. Therefore, with more up to date research, this study aimed to make a significant contribution to quantitatively summarize all the existing evidence and achieve a better understanding of the clinical significance of sarcopenia with regard to prognosis and postoperative complication prediction in patients with EC.…”
Section: Introductionmentioning
confidence: 99%